Root pressure–volume curve traits capture rootstock drought tolerance. (20th October 2021) - Bartlett, M K; Sinclair, G; Fontanesi, G; Knipfer, T; Walker, M A; McElrone, A J
Abstract: Background and Aims: Living root tissues significantly constrain plant water uptake under drought, but we lack functional traits to feasibly screen diverse plants for variation in the drought responses of these tissues. Water stress causes roots to lose volume and turgor, which are crucial to root structure, hydraulics and growth. Thus, we hypothesized that root pressure–volume (p–v) curve traits, which quantify the effects of water potential on bulk root turgor and volume, would capture differences in rootstock drought tolerance. Methods: We used a greenhouse experiment to evaluate relationships between root p–v curve traits and gas exchange, whole-plant hydraulic conductance and biomass under drought for eight grapevine rootstocks that varied widely in drought performance in field trials (101-14, 110R, 420A, 5C, 140-Ru, 1103P, Ramsey and Riparia Gloire), grafted to the same scion variety ( Vitis vinifera 'Chardonnay'). Key Results: The traits varied significantly across rootstocks, and droughted vines significantly reduced root turgor loss point ( π tlp ), osmotic potential at full hydration ( π o ) and capacitance ( C ), indicating that roots became less susceptible to turgor loss and volumetric shrinkage. Rootstocks that retained a greater root volume (i.e. a lower C ) also maintained more gas exchange under drought. The rootstocks that previous field trials have classified as drought tolerant exhibited significantly lower π tlp, π o and C values in well-watered conditions, but significantly higher π o and π tlp values under water stress, than the varieties classified as drought sensitive. Conclusions: These findings suggest that acclimation in root p–v curve traits improves gas exchange in persistently dry conditions, potentially through impacts on root hydraulics or root to shoot chemical signalling. However, retaining turgor and volume in previously unstressed roots, as these roots deplete wet soil to moderately negative water potentials, could be more important to drought performance in the deep, highly heterogenous rooting zones which grapevines develop under field conditions.